PENERAPAN MODEL PEMBELAJARAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS VII.A DI SMP NEGERI 19 KOTA MAKASSAR - Khairiah, Nabilatul; Abdul Wahab; Subaedah; Mustamin; Muhammad Syahrul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes of students in Islamic Religious Education and Character Building subject in class VII.A of SMP Negeri 19 Makassar. The problem was caused by the use of conventional teaching methods that made students less active and less interested in the learning process. This study aimed to describe the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model and to determine its effectiveness in improving students’ learning outcomes. This research employed Classroom Action Research (CAR) consisting of two cycles. Each cycle included four stages: planning, action, observation, and reflection. The subjects of this study were 29 students of class VII.A at SMP Negeri 19 Makassar. Data were collected through observation, interviews, documentation, and learning achievement tests. The results revealed that the implementation of the CIRC learning model successfully improved students’ learning outcomes. In the pre-cycle stage, the average score was 65.34 with a learning mastery percentage of 34.48%. In Cycle I, the average score increased to 80.52 with a mastery percentage of 65.52%. Furthermore, in Cycle II, the average score increased to 89.48 with a mastery percentage of 93.10%. These findings indicate that the CIRC learning model is effective in improving students’ learning outcomes in Islamic Religious Education and Character Building subject for class VII.A at SMP Negeri 19 Makassar.